Spatial Assessment of Groundwater Quality with Special Reference to Nitrate Pollution in Raipur City, Chhattisgarh State, India using Geographical Information System - Khan, Rubia; Jhariya, D.C. (International Journal of Advanced Geosciences, 2017)
Groundwater quality is one of the most important aspects for sustainable development of social and economic life. In present study, 41 groundwater samples were collected systematically during the pre-monsoon (May 2015) and post-monsoon (December 2015) periods. Nine parameters, i.e. EC, Ca, Mg, Na, K, NO3, SO4, HCO3 and Cl were analyzed in the laboratory adapting a standard protocol of APHA, 1995. The analyzed samples were compared with BIS and WHO standard for drinking purpose and spatial distribution map was prepared using Arc GIS Software. In present study, it is found that Ca, Mg, K and NO3 are above permissible limit and SO4 is above an acceptable limits according to BIS standard. Present study reflecting that main causes of groundwater pollution in study area are anthropogenic activities.